2010
DOI: 10.1080/10420150.2010.502171
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of the uranyl titanate mineral betafite (Ca,U)2(Ti,Nb)2O6(OH): effect of metamictization

Abstract: Raman spectra of the uranyl titanate mineral betafite were obtained and related to the mineral structure. A comparison is made with the spectra of uranyl oxyhydroxide hydrates. Observed bands are attributed to the (UO 2 ) 2+ stretching and bending vibrations, U-OH bending vibrations and H 2 O and (OH) − stretching, bending and libration modes. U-O bond lengths in uranyls and O − H · · · O bond lengths are calculated from the wavenumbers assigned to the stretching vibrations. Raman bands of betafite are compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The intense peak at 542 cm −1 and shoulder at 620 cm −1 was also described in by Frost et al [15] as elongation of U 3 O bonding and Ti O bonding respectively. The peak intensities of the aforementioned peaks were all similar to what was reported in Frost [15].…”
Section: Vibrational Spectroscopymentioning
confidence: 71%
See 3 more Smart Citations
“…The intense peak at 542 cm −1 and shoulder at 620 cm −1 was also described in by Frost et al [15] as elongation of U 3 O bonding and Ti O bonding respectively. The peak intensities of the aforementioned peaks were all similar to what was reported in Frost [15].…”
Section: Vibrational Spectroscopymentioning
confidence: 71%
“…The intense peak at 542 cm −1 and shoulder at 620 cm −1 was also described in by Frost et al [15] as elongation of U 3 O bonding and Ti O bonding respectively. The peak intensities of the aforementioned peaks were all similar to what was reported in Frost [15]. McConnell et al [30] showed Raman bands of Nb O in Nb 2 O 5 occurring at 704 cm −1 , this is consistent with observed bands in the synthetic betafite spectrum.…”
Section: Vibrational Spectroscopymentioning
confidence: 71%
See 2 more Smart Citations
“…4a and b. In previous work, the brannerite Raman spectrum has been thoroughly analysed between 100 cm À1 and 1100 cm À1 , with the vibration modes fitted by Raman data from known uranyl titanate minerals holfertite, davidite and betafite and from known uranyl oxyhydroxide minerals (Frost et al, 2009;Frost andReddy, 2010, 2011;Frost, 2011). As well, the RRUFF™ Project online database (http://rruff.info/) also contains reference spectra for a natural (RRUFF ID: R060613) and heated (RRUFF ID: R080091) brannerite sample sourced from Crockers Well.…”
Section: Raman Spectroscopymentioning
confidence: 99%